2020
DOI: 10.2147/ccid.s240784
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Preliminary Clinical Evaluation of a Topical Product for Reducing Slight Rosacea Imperfections</p>

Abstract: Introduction: Rosacea is a chronic multifactorial skin disorder mainly affecting facial skin with an estimated prevalence of about 5% worldwide. Its main symptoms, occurring early during pathology development, are skin dehydration, redness, erythema, and telangiectasia. Given the lack of a resolutive cure, therapeutic approaches able to relieve the main symptoms are needed. Purpose: The aim of this research article is to evaluate the beneficial effect of a topical product (Serum BK46) on rosacea symptoms. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The evaporimetry skin barrier measurement, TEWL, is validated and hence the best method for evaluation of skin barrier damage, 32 and the utility of the tool is confirmed by the continuous use of TEWL over decades as the primary outcome in several experimental studies evaluating the skin barrier response to for example SLS, ABHR, detergents, and topical products. 8,46 Numerous studies have shown that the skin barrier evaluated by TEWL after application of ABHR is unaffected as in accordance with our results. 6,8,9 However, Plum et al reported an increase in TEWL when the ABHR was applied on hydrated skin, which may mimic the real-life situation in busy work-settings in the health care sector.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The evaporimetry skin barrier measurement, TEWL, is validated and hence the best method for evaluation of skin barrier damage, 32 and the utility of the tool is confirmed by the continuous use of TEWL over decades as the primary outcome in several experimental studies evaluating the skin barrier response to for example SLS, ABHR, detergents, and topical products. 8,46 Numerous studies have shown that the skin barrier evaluated by TEWL after application of ABHR is unaffected as in accordance with our results. 6,8,9 However, Plum et al reported an increase in TEWL when the ABHR was applied on hydrated skin, which may mimic the real-life situation in busy work-settings in the health care sector.…”
Section: Discussionsupporting
confidence: 92%
“…have shown that the TEWL values were stable between 1 and 3 h after removal of patches 45 the measurements in our study were performed 1 h after patch removal. The evaporimetry skin barrier measurement, TEWL, is validated and hence the best method for evaluation of skin barrier damage, 32 and the utility of the tool is confirmed by the continuous use of TEWL over decades as the primary outcome in several experimental studies evaluating the skin barrier response to for example SLS, ABHR, detergents, and topical products 8,46 …”
Section: Discussionmentioning
confidence: 99%
“…Polyacrylate crosspolymer-6 is also pre-neutralized synthetic polymer acting as a gelling and stabilizing agent. This component could deposit over the outer layers of the skin because of its high molecular weight and thereby facilitate the formation of a barrier to prevent water loss and hydrate the skin [ 35 ]. The silicone-based emulsifier (dimethicone-based emulsifier) was used in the formulations as a texture and sensory modifier.…”
Section: Resultsmentioning
confidence: 99%
“…Rosacea is a chronic skin disorder characterized by erythema, flushing, telangiectasia, papules and pustules, phymatous changes, and ocular involvement. [1][2][3][4][5] In 2012, a standard classification system for rosacea was developed by the National Rosacea Society Expert Committee. Four distinct subtypes of rosacea were established: erythematotelangiectatic, papulopustular, phymatous, and ocular rosacea.…”
Section: Introductionmentioning
confidence: 99%